2006
DOI: 10.1002/ijc.22122
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of vegetable consumption and liver cancer in Japan

Abstract: We examined the relationship between vegetable consumption and the risk of death from liver cancer in a cohort study in Japan. This analysis is based on data from 6,049 subjects aged 40 to 79 years enrolled in a cohort study conducted in Fukuoka Prefecture, Japan. The follow-up period was from 1986 to 1999. All liver cancer deaths were recorded. The vegetable consumption was classified into 3 groups: ''once per week or less,'' ''2-4 times per week'' and ''daily intake.'' The Cox proportional hazards models wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…lasted for more than 5 years, and some of them followed subjects more than 10 years 24,25,26,29 . In one Japanese cohort study, the study population was atomic-bomb survivors in Hiroshima and Nagasaki 24 .…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…lasted for more than 5 years, and some of them followed subjects more than 10 years 24,25,26,29 . In one Japanese cohort study, the study population was atomic-bomb survivors in Hiroshima and Nagasaki 24 .…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…Importantly, Pham et al . [28]showed that the activation of JAK/STAT pathway participated in the tumorigenesis of gastric cancer. Ding et al .…”
Section: Discussionmentioning
confidence: 99%
“…Cohort studies from Taiwan and Japan observed a significant inverse association between vegetable and fruits consumption and risk of HCC (Yu et al, 1995;Sauvaget et al, 2003;Pham et al, 2006;Kurahashi et al, 2009). Based on available evidence, the World Cancer Research Fund (WCRF) concluded in 2007 that there was limited suggestive evidence for the protective effect of fruit against liver cancer and limited non-conclusive evidence for vegetables (WCRF, 2007).…”
Section: Dietary Factorsmentioning
confidence: 99%